The new economics of sovereign wealth funds - Castelli, Massimiliano (Hoboken Wiley, 2012)
Sovereign wealth funds (SWFs) aren't new, but they are often misunderstood. As they've attracted more attention over the last decade and grown greatly in size, the need for a new and thorough resource on SWFs has never been greater. These funds will only grow more important over the coming years. In this book, expert authors who work in the industry present a comprehensive look at SWFs from the perspective of western investors.
Includes bibliographical references (p. 189-198) and index.
Keywords: Sovereign wealth funds